대구, 경북 지역 Helicobacter pylori 일차 및 이차 치료의 연도별 제균율 변화 최근 9년 성적 - 조한진; Han Jin Cho; 배락천; Rack Cheon Bae; 이순학; Soon Hak Lee; 장선익; Sun Ik Jang; 이현석; Hyun Seok Lee; 최소영; So Young Choi; et al. (The Korean journal of medicine, 2009)
목적: 최근 H. pylori의 항생제 내성률이 증가하고 있으나, 각 지역별로 H. pylori 일차 삼제요법에 의한 제균율의 변화추세에 대한 연구가 부족한 실정이다. 이번 연구에서 대구 경북지역의 단일기관의 최근 9년간 H. pylori 제균율의 변화추세를 조사하였다. 방법: 1999년 1월부터 2007년 12월까지 H. pylori 양성으로 진단받고 일주일간 일차 제균 요법을 시행한 615명의 환자의 제균율을 연도, 궤양 위치에 따라 후향적으로 조사하였다. 결과: 전체 환자의 H. pylori 제균율은 81.6%였다. 궤양 위치와 PPI의 종류에 따른 제균율의 차이는 없었다. Per-protocol 분석에 의한 연도별 제균율은 1999, 2000, 2001, 2002, 2003, 2004, 2005, 2006, 2007년에 각각 76.3%, 78.3%, 82.8%, 88.5%, 77.8%, 91.7%, 84.8%, 75.4%, 83.7%였다. 최근 9년간 제균율의 차이는 없었다(p=0.760). 결론: 대구 경북지역에서 일차 제균 치료로서 PPI를 기본으로 하는 삼제 병합요법은 최근 9년 동안 제균율 변화 경향을 보이지 않아 아직까지 유용한 치료법으로 생각되나, 절대적인 치료효과가 낮아 향후 새로운 치료법을 찾기 위한 더 많은 연구가 필요할 것으로 생각한다. Background/Aims: The reported prevalence of antibiotic resistance in Helicobacter pylori infection has been increasing. However, recent trends in the eradication rates of H. pylori using first-line triple regimens are rarely reported. Therefore, we determined the trend in the H. pylori eradication rates in a single center for the most recent 9 years in Daegu and Kyungpook provinces, Korea. Methods: From January 1999 through December 2007, the eradication rates in 615 H. pylori-positive patients who received one-week triple regimens were evaluated retrospectively according to year and ulcer location. Results: The overall H. pylori eradication rate was 81.6%. The eradication rate from the years 1999 to 2007 was 76.3, 78.3, 82.8, 88.5, 77.8, 91.7, 84.8, 75.4, and 83.7%, respectively, based on the per-protocol analysis. No definite evidence of a decreasing tendency of the eradication rate was seen over the 9 years (p=0.760). Furthermore, there was no significant difference in the eradication rate according to ulcer location. Conclusions: There is no decreasing trend in the H. pylori eradication rate over the past 9 years in Daegu and Kyungpook provinces. However, the eradication rates are not satisfactory, and further investigation is needed to develop more effective regimens.